GC/Mass analysis of the volatile compounds of P. hyrcanicum diethyl ether extract and GC profiling of some Iranian Polygonum species - S. Saeidnia; P. Sarkhail; F Moradi-Afrapoli; A.R. Gohari; M. Nikan; N. Mokhber-Dezfuli; G.R. Amin; A. Hajiakhondi (Iranian Society of Pharmacognosy, 2014)
In this study, the relationship among four species of Polygonum (including P. hyrcanicum (three samples), P. persicaria, P. avicular, and P. hydropiper) was investigated by GC profiling. Furthermore, the major compounds of the ethylic ether extract of P. hyrcanicum were identified by GC/MS as: α-bisabolol (17.5%), cedrol (15.9%), sesquisabinene hydrate (13.0%), α-elemol (10.5%) and trans-longipinocarveol (10.1%). All the identified compounds were sesquiterpenes and no monoterpene, fatty acid and/or hydrocarbone were detected in the extract. Chemical distances among the mentioned species were calculated in order to construct the dendrogram of closely related samples. Results indicated that the distance between two samples of P. hyrcanicum was considered to be short and their GC profiles were quite similar to each other and also there was a close relationship between the two samples of Polygonum with P. avicular. P. hydropiper was observed far from the two samples of P. hyrcanicum in comparison to other samples. Interestingly, P. hyrcanicum, gathered from Veresk, had no close relationship with other pairs of P. hyrcanicum.The results of this study support the phylogenetic relationships among these Polygonum species which was previously reported.